Pronatalist policies and fertility in Russia: Estimating tempo and quantum effects - Asiya Validova (Comparative Population Studies (CPoS), 2021)
This paper examines the family policy reforms of 2007 in Russia that were aimed explicitly at encouraging second and higher-order births, and analyses their impact on fertility. The existing empirical findings about population policy interventions in transition economies are inconclusive, while the most common argument states that policies based on material incentives are insufficient to significantly raise the real fertility in a population. The study aims to offer a better insight to the following research question: was Russian demographic policy effective in terms of raising the fertility level in the country or did it merely change the timing of births? The objective of the paper is to measure two effects of the pronatalist policy in Russia: tempo effect and quantum effect. Using data from the Human Fertility Database, I employ the decomposition method to separate tempo and quantum effects in the observed total fertility rate, and I estimate their relative weight in observed fertility changes. The analysis of period fertility indicators confirmed the prevalence of a tempo effect in observed total fertility rate change, but also revealed a quantum effect of the policy measures, although this was much smaller. Policy impact varied by birth order. For second parity, the tempo effect played a more critical role, while for third parity the quantum effect was more important. Another decomposition approach employed to measure the contributions of various factors in the increase of the number of births during the post-reform period showed the quantum effect which was driven by second and third order births. The study provides empirical evidence of the impact of policies on fertility behaviour, expands the existing analysis of pronatalist measures taken in Russia, and contributes to our understanding of the role of tempo and quantum effects in the recent fertility change in Russia.
urn:nbn:de:bib-cpos-2021-15en7
Keywords: 300; Births; Fertility Rates; Pronatalist Policies; Russia; Tempo and Quantum Effects